Communication Support for Older Adults Through Pictograms - Arias-Flores, Hugo (2023)
Changes generated by the pandemic have stimulated new forms of communication through technological devices. Thanks to these, augmentative and alternative communication through the use of pictograms has allowed the development of communicative capacity for people who face health problems, such as speech, limited motor skills, hearing, among others. In particular, for segments of the elderly population with limited communication and technology management skills, it is important to consider usability and accessibility criteria in technological support interfaces design, in order to provide a satisfying and non-intrusive user experience. Support activities must be pleasant and transparent for the effective users’ communication with their environment. In this context, the article presents a methodology for the design of an augmentative communication solution based on pictograms, with the purpose of transmitting the message from the user to the receiver. This article proposes a systematic review of the literature on augmentative and alternative communication, as well as the use of existing pictograms and technologies. The systematic review protocol considered the choice of four digital libraries for the search. The method of search and selection of technological solutions was based on the search for Apps and websites for the use of pictograms through technology to automate and support the communication of elderly